Hunting Motion and Stability Analysis for the Railway Bogie with Lateral Switching Semi-Active Control - Zhang, Yaowen; Chen, Chunjun (Journal of Vibration Engineering & Technologies, 2025)
Purpose Introducing semi-active control (SAC) into railway vehicles can improve ride comfort but may also induce instability. However, SAC-induced railway vehicle instability has not received sufficient attention, hindering its practical application. This paper investigates the stability issues of railway bogies and full-vehicles equipped with lateral switching semi-active control (LSSAC), focusing on the impact of damping adjustment range (DAR) and switching laws. Methods First, a two-degree-of-freedom (DOF) rigid railway bogie model is developed, and its analytical solutions are derived. Based on these, the hunting behavior and the necessary and sufficient conditions for global asymptotic stability of the railway bogie with LSSAC are derived. Then, numerical results are presented to illustrate the hunting behavior and stability conclusions. Finally, the stability conclusions are extended to the full-vehicle through qualitative energy-based analysis and verified by comparing bifurcation diagrams and critical speeds. Results and Conclusions The results reveal that the combination of an excessive DAR and switching laws that reduce lateral damping near peak lateral deflection velocity is detrimental to the stability under LSSAC. This work provides an explanation for how LSSAC affects stability and identifies DAR and switching laws more prone to inducing instability, offering guidance for the design of SAC algorithms in railway vehicles. Graphical Abstract